Nazvy barev vprirovndnich v textech soućasne ćestiny (na materiale Ceskeho ndrodmho korpusu) - Kolářová , Ivana (Stylistyka, 2021)
There are parables with the names of colours in Czech that compare the “colour of people - of the human face, human skin”, of the colour of anything else to the colour of anything in naturę, of natural scenery: to the colour of plants (fiuty jako pampeliśka — as yellow as a dandelion, źluty jako citron — as yellow as a lemon / lemon coloured), to the colours of animals or birds (fiuty jako kanarek - as yellow as a canary / canary coloured) or to the colours of anything else in natural scenery (śedy jako morę - as grey as a billów, śedy jako hvezdny vecer/hvezdne nebe - as grey as an evening sky with stars), or the parables can compare the colour of the human body (face) to the colour of some things fiuty jako vosk — as yellow as a wax /, źluty jako pergamen - as yellow as vellum, źluty jako pivo - as yellow as a beer, śedy jako ocel — as grey as steel/steel-grey, śedy jako popel - as grey as ashes / cinereous). Authors of belles-lettres or of poetry using parable-comparison aROVAwith the words źluty / yellow usually depict the human visage as a symptom of illness or caducity (jeho oblićej byl źluty jako vosk - his face was yellow as wax’ byl źluty jako per- gamen - he wasyellow as vellum) or they etiolate the people (zuby mel źlutejako citron - his teeth were lemon yellowed, dostał źloutenku a byl źluty jako kanarek - he suffered from jaundice and was canary coloured). Using the word śedy / grey in parable-compari- son authors sometimes depict people of nasty appearance (oblićej śedy jako prach / jako popel - face as grey as dust // as ashes / cindereous), but sometimes they picture somet- hing nice in the human appearance (pći śede jako hvezdne nebe / jako morę / jako obld- zky - eyes as grey as an evening sky with stars / billowi pebbles).